Violence in context : current evidence on risk, protection, and prevention - Herrenkohl, Todd Ian. (New York ; Oxford : Oxford University Press, 2011)
Edited by four leading violence researchers, this book takes a systemic view, offering a critical appraisal of research and theory that focuses on violence in youth, families, and communities.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Youth and violence; Violence -- Prevention; Violence -- Social aspects